Acute liver failure caused by pembrolizumab in a patient with pulmonary metastatic liver cancer: A case report. Issue 51 (December 2017) - Wu, Zhenping; Lai, Lingling; Li, Ming; Zhang, Lunli; Zhang, Wenfeng
Abstract: Rationale: Keytruda (pembrolizumab) is an inhibitor of programmed cell death receptor-1 (PD-1), which was approved to treat advanced melanoma and nonsmall cell lung cancer patients who do not respond to other treatment. However, its efficacy and security in the treatment of advanced liver cancer is still under investigation. Patient concerns: A 60-year-old man was diagnosed with pulmonary metastatic liver cancer who accepted pembrolizumab treatment after the failure of sorafenib. When injected pembrolizumab, in spite of pulmonary metastatic lesion shrink, the patient experienced severe liver dysfunction. Diagnoses: Based on the features of the clinical signs and laboratory examination, the patient was diagnosed with pembrolizumab-induced immune-related hepatitis by excluding other etiologies and drug-induced side effects. Interventions: The patient received glucocorticoid and artificial liver (plasma exchange) therapy after failed conservative liver protection treatment. Outcomes: The patient's liver dysfunction continuously progressed and he finally died of liver failure and its complications during his hospitalization. Lessons: Pembrolizumab showed efficacy in an advanced hepatocellular carcinoma patient with lung metastases. However, it can generate immune-related adverse events such as immune-related hepatitis which can be lethal.